Efeito do nitrato e nitrito na corrosão das ligas de alumínio 2024 e 7050 em soluções de NaCl - Dutra, Conceição Aparecida Matsumoto [UNESP]; Dos Santos Rodrigues, Domingos Sávio [UNESP]; Pereira, Marinalda Claudete [UNESP]; Codaro, Eduardo Norberto [UNESP]; Nakazato, Roberto Zenhei [UNESP] (My University, 2002)
The 2024-T3 and 7050-T7 aluminium alloys electrochemical behavior has been studied in NaCl 5% neutral solutions and 0,1M concentration containing NO 3 - or NO 2 -. The current job supports corrosion research on aluminium alloys used in aeronautic industry. Open circuit potential, polarisation curves and electrochemical impedance spectroscopy techniques have been used. In chloride solutions, alloys corrosion takes place through a pitting mechanism. Added anions to aerated solutions do not possess inhibition effect. In deaerated solutions, nitrite has diminished anodic dissolution rate, probably by incorporating this anion in the oxide and/or hydroxide film.
Nitrate and nitrite effects on the corrosion of 2024 and 7050 aluminum alloys in NaCl solutions
Keywords: Aeronautic materials; Aluminium alloys; Corrosion; Open circuit potential; Aerospace engineering; Dissolution; Electrochemistry; Nitrates; Polarization; Sodium chloride; Aluminum alloys